2015
DOI: 10.1159/000371749
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus Open Obesity Surgery: A Meta-Analysis of Pulmonary Complications

Abstract: The clinical effects of laparoscopy in the pulmonary function of obese patients have been poorly investigated in the past. A systematic review was undertaken, with the objective to identify published evidence on pulmonary complications in laparoscopic surgery in the obese. Outcome measures included pulmonary morbidity, pulmonary infection and mortality. The random effects model was used to calculate combined overall effect sizes of pooled data. Data are presented as the odds ratio (OR) with 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
17
1
4
Order By: Relevance
“…They reported that patients undergoing esophagectomy or gastrectomy had the highest rate of postoperative pneumonia. A retrospective study of 185,328 obese patients undergoing surgery by Antoniou et al [31] reported the occurrence of postoperative pneumonia was lower for laparoscopic surgery compared to open surgery (0.5% vs. 1.1%). Furthermore, laparoscopic surgery also had a lower mortality rate (0.1% vs. 0.4%).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that patients undergoing esophagectomy or gastrectomy had the highest rate of postoperative pneumonia. A retrospective study of 185,328 obese patients undergoing surgery by Antoniou et al [31] reported the occurrence of postoperative pneumonia was lower for laparoscopic surgery compared to open surgery (0.5% vs. 1.1%). Furthermore, laparoscopic surgery also had a lower mortality rate (0.1% vs. 0.4%).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Boni et al reported that the immune system was better preserved and there was less proinflammatory cytokine response in all laparoscopic surgical procedures; consequently, the infection rate, including the pulmonary system infections, was lower in laparoscopic surgery than in open surgery [ 15 ]. Antoniou et al reported that, in obesity surgery, the obesity itself was a pulmonary risk factor for complications in the postoperative period, together with parameters such as incisional pain, diaphragmatic irritation, and hypoventilation; they reported less pulmonary complications in their patients who had undergone laparoscopic surgery [ 16 ]. In our study, we compared the chest radiographs obtained in the postoperative period and found that 34 patients developed atelectasis, 26 (76.5%) of whom belonged to the open surgery group and 8 (23.5%) to the laparoscopy group.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Boni et al reported that the immune system was better preserved and there was less proinflammatory cytokine response in all laparoscopic surgical procedures; consequently, the infection rate, including the pulmonary system infections, was lower in laparoscopic surgery than in open 10 surgery . Antoniou et al reported that, in obesity surgery, the obesity itself was a pulmonary risk factor for complications in the postoperative period, together with parameters such as incisional pain, diaphragmatic irritation, and hypoventilation; they reported less pulmonary complications in their patients who had undergone 7,11 laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%